Modulating emission properties in a host–guest colloidal quantum well superlattice - Yu, Junhong (2022)
Self-assembly of colloidal nanocrystals into ordered superlattices is a powerful approach to enable novel collective properties which are not available in individual colloids. However, to date, it remains a major challenge to develop a practical route to modulate such collective properties for potential photonic applications. Herein, it is shown that the collective emission properties in colloidal quantum well (CQW) superlattices, including emission color and anisotropy, can be effectively modulated in a binary host–guest architecture. The experimental and theoretical results reveal that excitons of the host (i.e., the undoped CQWs) generated by photoexcitation can be controllably harvested by the guest (i.e., the Cu-doped CQWs) for light emission, owing to an exciton hopping assisted exciton trapping process. Such a nano-building block with tunable collective optical properties may enlighten novel colloidal material-based photonic applications, including optical anti-counterfeiting, next-generation liquid crystal displays, and multifunctional biological markers.